Identifying Influence of Stress on Professionals Working in Building Construction in Kathmandu Valley - Adhikari, Dinesh; Adhikari, Riwaj; Dhakal, Saurab (NPRC Journal of Multidisciplinary Research, 2025)
Background: The construction industry in Kathmandu Valley plays a pivotal role in Nepal’s economic development but is characterized by demanding work environments, rapid technological changes, and increasing business pressures. These factors have led to heightened stress among professionals, impacting their mental and physical well-being. Excessive workloads, unclear roles, limited support, and lack of autonomy are common stressors that affect job satisfaction and productivity. Despite the prevalence of stress in this sector, there has been limited research focused on its causes, effects, and management strategies within Nepal’s construction industry. This thesis aims to fill that gap by investigating the influence of stress on building construction professionals in Kathmandu Valley, identifying key stressors, examining their impacts, and recommending effective approaches for stress management to enhance employee well-being and organizational performance.Objectives: This study aims to identify key stressors affecting health and performance, examine stress effects on individual well-being and organizational outcomes, investigate stress prevalence among different professional roles, and recommend techniques to mitigate work stress impacts for construction professionals in Kathmandu Valley.Methods: The study used a mixed-methods approach, combining both qualitative and quantitative research methods. Data was collected through semi-structured questionnaires and in-depth interviews with construction professionals, and the results were analyzed using statistical tools such as descriptive analysis, correlation analysis, and t-tests to examine the causes and impacts of stress.Findings: The study found that construction professionals in Kathmandu Valley experience significant stress due to factors such as heavy workloads, tight deadlines, and lack of organizational support, which negatively impact their mental and physical well-being. While a strong positive correlation was observed between job stress and outcomes like anxiety, fatigue, depression, and dissatisfaction, the t-test analysis indicated no significant predictive relationship between low self-esteem and these stress-related outcomes. The research highlights the urgent need for effective stress management strategies in the construction sector to enhance employee well-being and organizational performance.Conclusion: The study concludes that job stress is a significant and pervasive issue among professionals working in building construction in Kathmandu Valley, primarily driven by factors such as excessive workloads, tight deadlines, and inadequate organizational support. While stress is found to have a strong correlation with negative outcomes like anxiety, fatigue, depression, and job dissatisfaction, the research did not establish a significant predictive link between low self-esteem and these stress-related effects. Ultimately, the thesis emphasizes the urgent need for construction organizations to recognize stress as a critical concern and to implement effective stress management strategies, fostering a healthier and more productive work environment for their employees.Novelty: It systematically explores the specific causes, effects, and management of job stress among building construction professionals in Kathmandu Valley using both quantitative and qualitative data. Unlike previous studies, it applies statistical analyses to directly examine the relationship between low self-esteem and stress outcomes, revealing that while correlations exist, predictive causation is not significant. The research provides new, locally relevant insights and practical recommendations for stress management tailored to Nepal’s dynamic construction sector.